Clinical and molecular epidemiology of human listeriosis in Taiwan. (March 2021) - Huang, Yu-Tsung; Kuo, Yao-Wen; Lee, Meng-Rui; Tsai, Yu-Huan; Teng, Lee-Jene; Tsai, Mao-Song; Liao, Chun-Hsing; Hsueh, Po-Ren
Highlights: Three major mutilocus sequence types were identified as causing human listeriosis in Taiwan (ST87, ST155 and ST378). Underlying conditions and clinical presentations of non-perinatal listeriosis were similar to western countries with high 30-day mortality (25.2%). Age, concurrent steroid usage and respiratory distress at presentation were associated with 30-day mortality. Abstract: Objective: To determine serogroups, multilocus sequence typing (MLST) of Listeria monocytogenes isolates and analyze clinical characteristics of these clones focusing on non-perinatal cases. Methods: From 2000 to 2015, we analyzed 123 human listeriosis cases at a medical center in northern Taiwan using PCR serogrouping, MLST, and clinical presentations. Results: The annual incidence of listeriosis increased since 2005 with a peak in 2008 (0.2 per 1000 admission) and decreased thereafter. Of the 115 non-perinatal listeriosis cases, we found a male predominance (60%) with an average age of 63.9 years old (standard deviation: 15.3 years), and almost all patients had underlying conditions including malignancies (61.7%), steroid usage (39.1%), diabetes mellitus (31.3%), renal insufficiency (27.8%), and liver cirrhosis (17.4%). Clinical presentations included bacteremia (74.8%), neurolisteriosis (20.0%), and spontaneous bacterial peritonitis (5.2%). The most frequently identified serogroup-sequence types (ST) were IIB-ST87 (30.9%), followed by IIA-ST378 (16.3%) and IIA-ST155 (14.6%). The 30-day all-cause mortality of non-perinatal listeriosis was 25.2% and was associated with age (Hazard ratio: 1.04, 95% C.I. = 1.01–1.07, p = 0.021), steroid usage (Hazard ratio: 2.54, 95% C.I. = 1.06–6.11, p = 0.038) and respiratory distress at presentation (Hazard ratio: 2.59, 95% C.I. = 1.05–6.39, p = 0.038); while no association was found with serogroups (IIA, IIB, and IVB) or three major ST types by multivariable analysis. All 8 mothers of perinatal listeriosis patients survived and three neonates died (mortality, 37.5%), and IIB-ST87 was the major type (62.5%). Conclusion: Predominant strains in Taiwan could cause significant morbidity and mortality. Further disease monitoring and source surveillance are warranted despite a declining trend of human listeriosis in Taiwan.